2022
DOI: 10.1186/s40337-022-00664-0
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring psychotic and eating disorders in England: findings from the 2014 Adult Psychiatric Morbidity Survey

Abstract: Background Psychotic disorders and eating disorders are complex mental illnesses associated with increased mortality and functional impairment. This study aimed to investigate the co-occurrence and relationships between eating disorders and psychotic disorders and assess the mediation effect of mood instability. Methods This study used data from the Adult Psychiatric Morbidity Survey (APMS) 2014, a general population-based survey in England. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In particular, impaired sleep in the form of either insomnia or hypersomnia and sometimes both, are extremely common is psychosis indicating the presence of circadian rhythm alterations (15,16). Hypersexuality is frequently encountered in patients with mania and those with bipolar schizoaffective disorder while eating disorder, either anorexia or bulimia,are common in psychosis with emphasis on mood disorders (17) .…”
Section: The Evolvement Of the Conceptmentioning
confidence: 99%
“…In particular, impaired sleep in the form of either insomnia or hypersomnia and sometimes both, are extremely common is psychosis indicating the presence of circadian rhythm alterations (15,16). Hypersexuality is frequently encountered in patients with mania and those with bipolar schizoaffective disorder while eating disorder, either anorexia or bulimia,are common in psychosis with emphasis on mood disorders (17) .…”
Section: The Evolvement Of the Conceptmentioning
confidence: 99%
“…Findings from clinical studies showed a high prevalence of comorbidity between psychotic disorders and EDs (Khalil et al, 2011; Kouidrat et al, 2014). One of the largest population-based studies on the topic was conducted in England (i.e., the Adult Psychiatric Morbidity Survey) (Rodgers et al, 2022), and demonstrated that community adults (mean age = 52.3 years) categorized as either with probable or diagnosed psychoses reported significantly more EDs than healthy controls without psychosis. A recent systematic review encompassing 31 studies and 471,158 participants showed elevated rates of binge eating symptoms (8.9%–45%), food craving (16.1%–64%), food addiction (27%–77.4%), night eating (4%–30%), and disordered eating behaviors (10%–41.5%) among individuals with schizophrenia spectrum disorders ( N = 2,651) (Sankaranarayanan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Possible shared pathophysiological pathways have also been hypothesized, including dopamine dysfunction, which is an established feature of psychotic disorders (Howes et al, 2012) and a previously described characteristic associated with EDs (Barry & Klawans, 1976; Frank et al, 2018). Other potential risk factors known to be implicated in both PEs and EDs have been proposed as mechanisms linking the two entities, such as cognitive impairments (e.g., deficits in visuospatial and global/local processing [Madsen et al, 2013; Watson, 2013]), mood instability (Rodgers et al, 2022), as well as reduced cognitive and emotional control (Hauser et al, 2011). In an attempt to explain in greater depth the relationship between EDs and psychosis, Seeman (2014) delineated seven hypotheses, including that body image distortions of EDs would represent delusional-like experiences related to psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Is it a misperception of body image as Bruch alluded to [ 17 ], or a psychotic illness? [ 18 ]. Is it a phobia of normal body weight as Crisp described?…”
mentioning
confidence: 99%